Highly sensitive and selective optical detection of Staphylococcus aureus using thiol functionalized monolayer tungsten disulfide grown by chemical vapor deposition - Abdul Kaium Mia; Swapnil Sinha; P.K. Giri (Sensors and Actuators Reports)
Monolayer tungsten disulfide (1L-WS2) exhibits excellent optical properties due to its direct bandgap. The extraordinary photoluminescence (PL) emission at room temperature from CVD-grown 1L-WS2 was utilized for the first time here as a recognition tool for detecting S. aureus bacteria with high sensitivity and selectivity. The 1L-WS2 possesses sulfur vacancy, which has been utilized for single-standard DNA (ssDNA) aptamer immobilization via the thiol functional group. The small-sized, highly selective ssDNA aptamers identify and selectively interact with targeted S. aureus, enabling selective detection. Interestingly, the PL emission of 1L-WS2 is strongly influenced by external charge doping. The shape of the PL emission peak of 1L-WS2 undergoes significant changes in the presence of targeted S. aureus as a result of charge transfer originating from selective interactions between ssDNA aptamer and S. aureus, while it remains unaffected for non-targeted Escherichia coli. The ratio of the integrated intensities of trion to neutral exciton peak was used as a calibration parameter for the quantification of S. aureus concentrations. The PL analysis of 1L-WS2 with increasing concentration of S. aureus exhibits a linear response over 102 CFU/mL to 107 CFU/ml with a lower detection limit of 2.0 CFU/mL. The proposed sensing system can identify an unknown concentration of S. aureus in human urine with 78% accuracy at a concentration of 105 CFU/mL. These results demonstrate the potential future generation applications of monolayer transition metal dichalcogenides in the optical biosensing of pathogenic species using suitable receptors.